Cytopathological profile of women metinthe basic units of the Municipality of Uruguaiana, RS - Ströher, Deise Jaqueline; Aramburu, Thais D.B.; Abad, Marta Aurora S.; Nunes, Vinícius T.; Manfredini, Vanusa (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Introduction:cancer of the cervix has been named as the third most common type of cancer among women and its relation to infection by human papillomavirus (HPV) is well established. objective: cytopathologic know the profile of women attending the Basic Health Units in the municipality of Uruguaiana, RS. Methods:retrospective analysis of cross-sectional and descriptive the reports of cytopathology from patients who underwent gynecologic cytology (Papanicolaou) and their medical records, issued between the years 2003 and 2011. We selected the variables related to age and change and cytopathological sorted by Bethesda, 2001. results:of all reports of reports of cytopathology analyzed, 15.5% have a cell phone and some change with the highest prevalence was atypical squamous cells of undetermined significance (ASC-US), with 50.28%, followed by low-grade intraepithelial lesions (LSIL), with 35.45%. In both cases, women younger than 25 years showed the highest prevalence. About 13% of patients had HPV infection and the highest prevalence was observed in the age group below 25 years (47.84%). Conclusion: the age group with the highest prevalence of cervical lesions in women is under the age of 25 years and many of the cellular changes associated with HPV infection. It is noteworthy, therefore, the need for political screening of cervical lesions in women in this age group, thus preventing the progression of lesions that evolve to cancer.